Monetary Discounting of Delayed Consequences Predict Employment Nudity: Exotic Dancers Versus Waitresses. Issue 2 (3rd April 2018) - Dixon, Mark R.; Speelman, Ryan C.; Rowsey, Kyle E.; Whiting, Seth W.; Buono, Frank D.; Daar, Jacob H.; Belisle, Jordan
ABSTRACT: The present study examined temporal monetary discounting rates among exotic dancers, waitresses who are required to wear revealing uniforms, and waitresses at a local restaurant where revealing clothes are not part of work attire. Current findings indicate that exotic dancers and waitresses who are required to wear revealing clothing discounted significantly more than waitresses at restaurants where provocative dress is not required. These results suggest that the type of job held may predict impulsivity, with nude or risqué occupations indicating steeper patterns of overall discounting.